Medi-Care Database Maintenance System - M. Keerthana, S.; Priyanga Devi, L.; Kavinya, D.; Sharmila, N. (International Journal of Engineering and Technology, 2018)
The recent advances in information and communication technology are congregation; storage and information sharing are simple and faster. We propose the architecture that guarantees the personal exchange of knowledge between patients and doctors through the SAS (storage aggregation server) by using asymmetric cryptography, the encoding technique. The random key enhances the security for the biomedical data of each patient. We introduce the concept of double-phase micro aggregation to restrict the intruder entities without the loss of information. We have derived that double phase multivariate micro aggregation properly and also the reduction of memory storage.Â Â